Intraoperative evaluation of blood flow for soft tissues in orthopaedic surgery using indocyanine green fluorescence angiography: A pilot study - Doi, N. (Bone Joint Res, 2019)
OBJECTIVES: Indocyanine green (ICG) fluorescence angiography is an emerging technique that can provide detailed anatomical information during surgery. The purpose of this study is to determine whether ICG fluorescence angiography can be used to evaluate the blood flow of the rotator cuff tendon in the clinical setting. METHODS: Twenty-six patients were evaluated from October 2016 to December 2017. The participants were categorized into three groups based on their diagnoses: the rotator cuff tear group; normal rotator cuff group; and adhesive capsulitis group. After establishing a posterior standard viewing portal, intravenous administration of ICG at 0.2 mg/kg body weight was performed, and fluorescence images were recorded. The time from injection of the drug to the beginning of enhancement of the observed area was measured. The hypovascular area in the rotator cuff was evaluated, and the ratio of the hypovascular area to the anterolateral area of the rotator cuff tendon was calculated (hypovascular area ratio). RESULTS: ICG fluorescence angiography allowed for visualization of blood flow in the rotator cuff in all groups. The adhesive capsulitis group showed significantly earlier enhancement than the other groups. Furthermore, the adhesive capsulitis group had a significantly smaller hypovascular area ratio than the other groups. CONCLUSION: ICG fluorescence angiography allowed for evaluation of real-time blood flow of the rotator cuff in arthroscopic shoulder surgery. The techniques of ICG fluorescence angiography are simple and easy to observe, observer reliability is high, and it has utility for evaluating blood flow during surgery. Cite this article: N. Doi, T. Izaki, S. Miyake, T. Shibata, T. Ishimatsu, Y. Shibata, T. Yamamoto. Intraoperative evaluation of blood flow for soft tissues in orthopaedic surgery using indocyanine green fluorescence angiography: A pilot study. Bone Joint Res 2019;8:118–125. DOI: 10.1302/2046-3758.83.BJR-2018-0151.R1.